Homeostatic Depression Shows Heightened Sensitivity to Synaptic Calcium - Yeates, Catherine J.; Frank, C. Andrew (Frontiers in Cellular Neuroscience, 2021)
Synapses and circuits rely on homeostatic forms of regulation in order to transmit meaningful information. The Drosophila melanogaster neuromuscular junction (NMJ) is a well-studied synapse that shows robust homeostatic control of function. Most prior studies of homeostatic plasticity at the NMJ have centered on presynaptic homeostatic potentiation (PHP). PHP happens when postsynaptic muscle neurotransmitter receptors are impaired, triggering retrograde signaling that causes an increase in presynaptic neurotransmitter release. As a result, normal levels of evoked excitation are maintained. The counterpart to PHP at the NMJ is presynaptic homeostatic depression (PHD). Overexpression of the Drosophila vesicular glutamate transporter (VGlut) causes an increase in the amplitude of spontaneous events. PHD happens when the synapse responds to the challenge by decreasing quantal content during evoked neurotransmission – again, resulting in normal levels of postsynaptic excitation. We hypothesized that there may exist a class of molecules that affects both PHP and PHD. Impairment of any such molecule could hurt a synapse’s ability to respond to any significant homeostatic challenge. We conducted an electrophysiology-based screen for blocks of PHD. While we did not observe a block of PHD in the genetic conditions screened, we instead found loss-of-function conditions that led to excess depression – i.e., a substantial deficit in evoked amplitude when combined with VGlut overexpression. The conditions causing this phenotype included a double heterozygous loss-of-function condition for genes encoding the inositol trisphosphate receptor (IP3R – itpr) and ryanodine receptor (RyR). IP3Rs and RyRs gate calcium release from intracellular stores. Pharmacological agents targeting IP3R and RyR recapitulated the genetic losses of these factors, as did lowering calcium levels from other sources. Our data are consistent with the idea that some factors required for homeostatic potentiation are also required for the synapse to achieve appropriate levels of homeostatic depression. Loss of such factors may disorient compensatory plasticity signals.